Experimental conditions affecting the sensitivity of enzyme-linked immunosorbent assay (ELISA) for detection of hepatitis B surface antigen (HBsAg) - Fields, Howard A. (1983)
The sensitivity of an enzyme-linked immunosorbent assay (ELISA) for the detection of hepatitis B surface antigen (HBsAg) was improved 16 to 32 times after examination of various solid-phase supports, different antibody preparations as capture antibody, and different conditions for adsorbing capture antibody to the solid-phase. Comparisons were made by checkerboard titration analysis and by sensitivity studies, both of which demonstrated essentially equivalent results. Endpoints were determined by visual inspection and by spectrophotometry using o-phenylenediamine as substrate. The assay was as sensitive as commercially available radioimmunoassays without the requirement of affinity chromatography purified reagents, expensive instrumentation, or radioisotopes.